Microbiological colonization of the pancreatic tumor affects postoperative complications and outcome after pancreatic surgery - Biesel, Esther Anna; Sundheimer, Johanna; Badr, Mohamed Tarek; Posadas-Cantera, Sara; Chikhladze, Sophia; Fichtner-Feigl, Stefan; Wittel, Uwe Alexander (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundThe patient´s microbiome has become a focal point in cancer research. Even for pancreatic cancer, alterations in the microbiome appear to influence cancer formation and progression. The aim of our single-center analysis was the examination of microbiological colonization of pancreas tissue at the time of surgery and its potential influence on complications and outcome.MethodsWe prospectively evaluated patients undergoing pancreatic surgery over a three-year period from June 2018 to June 2021. We focused on the microbiological colonization of pancreatic tissue which was acquired during pancreatic surgery. Tissue samples were cultivated at our institute of microbiology. Patients´ characteristics, complications and postoperative outcome were analyzed using a prospectively maintained SPSS database.ResultsBetween June 2018 and June 2021, we collected pancreatic tissue samples of a total of 178 patients undergoing pancreas resections, mostly due to ductal adenocarcinoma (PDAC; 50.6%). We could cultivate bacterial or fungal species in pancreatic tissue samples of 50 of our patients (28.1%). The majority of cases were characterized by the presence of a single microbial species, but 20 patients (11.2%) showed colonization with up to four different species. Among the bacterial species detected were Enterococcus faecium, Enterococcus faecalis, Escherichia coli, Staphylococcus aureus, Enterobacter cloacae and Klebsiella pneumonia. We found significantly more microbiological culture growth in patients with a preoperative biliary stent (74.0% vs. 15.6%, p < 0.001). Concerning postoperative complications, we found no difference concerning pancreatic fistula, but colonization with E. coli was associated with a significantly higher rate of postpancreatectomy hemorrhage (30.0% vs. 8.9%, p = 0.032). Interestingly, survival of PDAC patients seems to be negatively affected by positive microbiological findings at the time of surgery, but without reaching statistical significance (p = 0.770).ConclusionIn this first analysis of our patient cohort, we could show a microbiological colonization of pancreatic tumor tissue in almost a third of our patients. There seems to be only a minor impact on postoperative complications, but long-term outcome seems to be worse in patients with a positive pancreas microbiome. Further observation is needed to evaluate the influence of the tumor microbiome on the long-term oncological outcome in PDAC patients.